2004
DOI: 10.1111/j.0014-3820.2004.tb01699.x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Selection and the Organ-Specific Differentiation of Hiv-1 V3 Hypervariable Region

Abstract: Abstract. The existence of organ-specific HIV-1 populations within infected hosts has been studied for many years; nonetheless results reported by different authors are somewhat discrepant. To tackle this problem, we used a population genetics approach to analyze previously published data from the V3 hypervariable region of the envelope env gene. Our results are compatible with a population subdivision by organs in 95% of individuals analyzed at autopsy. In addition, populations infecting the nervous system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…Divergence typically functions on a longer time scale during which natural selection may have a more important role in the ultimate fixation of mutations. Our results are in concordance with those recently reported by both Templeton et al (2004) and Sanjuán et al (2004), collectively stressing the necessity of evaluating mutation, natural selection, and recombination in the context of population structure. We are currently exploring the construction of a composite model that can be evaluated in a fully Bayesian framework.…”
Section: Discussionsupporting
confidence: 93%
“…Divergence typically functions on a longer time scale during which natural selection may have a more important role in the ultimate fixation of mutations. Our results are in concordance with those recently reported by both Templeton et al (2004) and Sanjuán et al (2004), collectively stressing the necessity of evaluating mutation, natural selection, and recombination in the context of population structure. We are currently exploring the construction of a composite model that can be evaluated in a fully Bayesian framework.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown tissue-specific variations in different viral models, including arenavirus sequences isolated from the same animal (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). To avoid this bias, ML29 was isolated only from sera of vaccinated animals.…”
Section: Discussionmentioning
confidence: 99%
“…In the analyses, cerebrospinal fluid (CSF) virus was used as an investigative surrogate for brain-derived HIV-1. Although indirect, this strategy is validated by phylogenetic evidence that CSF and brain-derived viral populations are more closely related to each other than to populations derived from other body compartments [92]. We hypothesized that detailed analyses of full-length HIV-1 env (>2.5Kb) would allow for the identification of genetic characteristics associated with the presence of viral variants in the CNS.…”
Section: Discussionmentioning
confidence: 99%